Evaluation Of The Relationship Between Interpersonal Communication Competence And Intercultural Communication Competence Among Postgraduate Students From Different Nationalities - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab (University Putra Malaysia (UPM), 2017)
This study was conducted to evaluate the relationship between interpersonal communication competence and intercultural communication competence among postgraduate students from different countries with different cultural backgrounds. A mixed method research design which includes both the quantitative and qualitative methods was applied to carry out this study. This study had 125 participants from 17 different countries. All participants of this study were postgraduate students and were living in a multicultural university campus. The results from this study confirmed that the levels of interpersonal communication competence and intercultural communication among individuals from different nationalities who live in a diverse environment have close relationship and significantly affect one another. Based on the results of the study, the good level of interpersonal communication competence encourages and enables individuals to be involved in interactions with their peers from different backgrounds and gain some new social and cultural information. According to the results of this study, interactions among individuals from different backgrounds help them to improve both of their interpersonal communication competence and intercultural communication competence. The results from this study may add some new and interesting information in the literature.